The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jam.12559
|View full text |Cite
|
Sign up to set email alerts
|

ViableLegionella pneumophilabacteria in natural soil and rainwater puddles

Abstract: Aims For the majority of sporadic Legionnaires’ disease cases the source of infection remains unknown. Infection may possible result from exposure to Legionella bacteria in sources that are not yet considered in outbreak investigations. Therefore, potential sources of pathogenic Legionella bacteria—natural soil and rainwater puddles on roads—were studied in 2012. Methods and Results Legionella bacteria were detected in 30% (6/20) of soils and 3·9% (3/77) of rainwater puddles by amoebal coculture. Legionella pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…As L. pneumophila cycles through over at least 15 species of diverse protozoa in the environment (Rowbotham, ; Fields, ; Solomon et al , ; Molmeret et al , ), acquisition of LME‐1 would likely confer a costly host range switch under environmental conditions of sufficient host diversity. Note that this could occur within freshwater, the typical habitat of L. pneumophila (Fliermans et al , ), as Dictyostelium species have been observed in lakes and sediment (O'Dell, ; Richards et al , ; Somboonna et al , ; Shanan et al , ); at the same time, L. pneumophila has also been isolated from soil (Wallis and Robinson, ; Schalk et al , ; van Heijnsbergen et al , ), a long‐established habitat of D. discoideum (Singh, ). While D. discoideum is generally thought of within the context of a laboratory model for Legionella infection, these data suggest that further scrutiny should be placed on the natural association of L. pneumophila and D. discoideum in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…As L. pneumophila cycles through over at least 15 species of diverse protozoa in the environment (Rowbotham, ; Fields, ; Solomon et al , ; Molmeret et al , ), acquisition of LME‐1 would likely confer a costly host range switch under environmental conditions of sufficient host diversity. Note that this could occur within freshwater, the typical habitat of L. pneumophila (Fliermans et al , ), as Dictyostelium species have been observed in lakes and sediment (O'Dell, ; Richards et al , ; Somboonna et al , ; Shanan et al , ); at the same time, L. pneumophila has also been isolated from soil (Wallis and Robinson, ; Schalk et al , ; van Heijnsbergen et al , ), a long‐established habitat of D. discoideum (Singh, ). While D. discoideum is generally thought of within the context of a laboratory model for Legionella infection, these data suggest that further scrutiny should be placed on the natural association of L. pneumophila and D. discoideum in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the bacteria in the soil may come from industrial waste or cooling towers, Rowbotham 111 suggested that amoebae in soil might enhance the growth of Legionella . Other potential sources include rainwater puddles, which have been found to harbor viable L. pneumophila , 112 and rooftop rainwater cisterns. 113-116 Legionella appears to be part of the natural aquatic microbiome, as it has been found in oceans, lakes, and rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2000 and 2010, only 2.3% of the isolates (2/86) in the Belgian database were ST48 [17] and this was the first isolation of ST48 since 2008. The source of these isolates has never been determined, suggesting that these strains may be present in particular environmental niches unexplored so far [31][32][33][34][35]. The importance of these niches may be underestimated, as they may not yet be considered in source investigations and fall outside the legislative framework for (high) risk installations.…”
Section: Data Collection Management and Analysis To Generate The Hypmentioning
confidence: 99%